Tiktok and Beauty in the Age of Gen Z: A Baudrillard Economic Sociological Analysis - Harahap, Rahma Hayati; Asengbaramae, Rowiyah; Karindra, Nadia Aulia (Journal of Sustainable Economics, 2024)
Through influencers and E-WoM, TikTok creates a favourable environment for users in adapting and trying new things, both in terms of consuming products and marketing products. Through Baudrillard's theory, it can be seen that Gen Z consumption culture is influenced by their self-representation on social media. The background of this research lies in a shift in the paradigm of beauty consumption in the era of Generation Z. TikTok users quickly promoted and adopted a variety of beauty trends, creating a foundation for understanding the symbolic meaning created by the Gen Z consumption culture. The theory used is Jean Baudrillard's theory of consumer society. In this theory, consumer society no longer consume objects based on exchange values or usage values, but because of symbolic values which are abstract and constructed in nature. This article uses a literary study research method that involves searching and critically analysing relevant literature related to the title of the article. This study aims to explain Gen Z consumption culture on Tiktok beauty trend through Baudrillard's sociological economic perspective. Therefore, this article not only explains the beauty trends that are emerging in TikTok, but also opens up a discussion about how tikTok contributes to the formation of Gen Z identity and consumption culture.